Human Cloning from the Viewpoint of Figh and Ethics - Mohaghegh Damad, Seyyed Mostafa (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
Muslim Scholars and Islamic official Institutions consider human cloning as opposing religious doctrine, and forbidden. Their Ideas are based upon some theological and juridical arguments, including: posing a challenge to the creative power of God, breaking the tradition of marriage, breaking the tradition of diversity in creatures or species, making changes in divine creatures, game with creatures and so on. They as well refer to some verses of holy Quran,and take consequences against the permission of human cloning . The author is going to say that the above mentioned arguments are not coincided with the traditional method of Islamic juridical reasoning (Al-Ijtehad). The author offers some general solutions for formulating Islamic doctrines in the field of human cloning.